Pulmonary physician consultancy in emergency services in Turkey (PUPCEST) - a prospective multicenter study - Diken, Ozlem Ercen; Ekici, Aydanur; Bektas, Hayriye; Yildiz, Hanifi; Tabaru, Ali; Ogan, Nalan; Ozlu, Tevfik (European Respiratory Soc Journals Ltd, 2018)
[Abstract Not Available]
28th International Congress of the European-Respiratory-Society (ERS) -- SEP 15-19, 2018 -- Paris, FRANCE